Sincerity in Politics and International Relations - Baiasu, Sorin; Loriaux, Sylvie (Routledge Advances in International Relations and Global Politics, 2017)
This work examines concept of sincerity in politics and international relations in order to discuss what we should expect of politicians, within what parameters should they work, and how their decisions and actions could be made consistent with morality. The collection features an international cast of authors who specialize in the topic of sincerity in politics and international relations. Each chapter will be focused on a contemporary issue in politics and international relations, including corruption, public hypocrisy, cynicism, trust, security, policy formulation and decision-making, political apology, public reason, denial and self-deception,and will argue against the background of a Kantian view of sincerity as unconditional. Focusing on sincerity bearing on political actions, practices, and institutions at national and international level.